2011
DOI: 10.1186/1471-2148-11-189
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the reef fish Cephalopholis argus(Epinephelidae) indicates Pleistocene isolation across the indo-pacific barrier with contemporary overlap in the coral triangle

Abstract: BackgroundThe Coral Triangle (CT), bounded by the Philippines, the Malay Peninsula, and New Guinea, is the epicenter of marine biodiversity. Hypotheses that explain the source of this rich biodiversity include 1) the center of origin, 2) the center of accumulation, and 3) the region of overlap. Here we contribute to the debate with a phylogeographic survey of a widely distributed reef fish, the Peacock Grouper (Cephalopholis argus; Epinephelidae) at 21 locations (N = 550) using DNA sequence data from mtDNA cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
136
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(159 citation statements)
references
References 90 publications
(102 reference statements)
14
136
0
1
Order By: Relevance
“…The reconstruction points to a barrier, or series of barriers that have historically affected lineages from the Late Miocene, with an increasing impact towards the end of the Pliocene. The ongoing nature of this barrier may be evident in rspb.royalsocietypublishing.org Proc R Soc B 280: 20131541 population studies across the two regions, with temporal clades containing haplotypes from both regions [43,66]. However, the nature and location of the barrier is hard to identify.…”
Section: (Iii) East Pacific Barriermentioning
confidence: 99%
“…The reconstruction points to a barrier, or series of barriers that have historically affected lineages from the Late Miocene, with an increasing impact towards the end of the Pliocene. The ongoing nature of this barrier may be evident in rspb.royalsocietypublishing.org Proc R Soc B 280: 20131541 population studies across the two regions, with temporal clades containing haplotypes from both regions [43,66]. However, the nature and location of the barrier is hard to identify.…”
Section: (Iii) East Pacific Barriermentioning
confidence: 99%
“…Most of the past research supports the Center of Origin hypothesis (Barber et al 2006, Williams 2007, Timm & Kochzius 2008, Nuryanto & Kochzius 2009). In contrast, relatively few cases substantiate the Center of Overlap (Teske et al 2005, Gaither et al 2011) and Center of Accumulation hypotheses (Wilson et al 2001, Drew & Barber 2009). Barber (2009 suggested that the central West Pacific's diversity is likely the result of multiple evolutionary processes, working either simultaneously or over different time periods, being dominated by different processes.…”
Section: Origin Of Pomacentrus Coelestismentioning
confidence: 99%
“…to sea level fluctuations, island emersion and submergence). These barriers mainly act on species displaying dispersal potential through the marine environment as larvae, juveniles or adults (Gaither et al 2010(Gaither et al , 2011. This is, for example, the case for many fish (Briggs 1974, Planes & Fauvelot 2002, Bay et al 2004, Craig et al 2007, Gaither et al 2010, Winters et al 2010) and invertebrates (Lavery et al 1995, Lessios et al 2001, 2003, Barber et al 2002 across the Indo-Malay archipelago, widely recognised as the Indo-Pacific Barrier (IPB; an intermittent barrier of throughflow current and chain of islands, depending on sea level fluctuations over the geological time scale) that separates the Indian and the Pacific Oceans.…”
Section: Introductionmentioning
confidence: 99%